ASPECT & EFFECT OF CORPORATE SOCIAL RESPONSIBILITY - SHRUTI MAGGO; DR. HEMANT KUMAR HARIT (Innovative Research Thoughts, 2021)
The corporate culture has long been one of "Wealth Creation." However, the development of multinational firms has given this perspective of view a fresh, larger perspective. And that is what the corporate entities mean by "social responsibility." Instead than just "making money," organizations should prioritize "building values." The conventional concept of "Corporate Financial Responsibility" has essentially given way to a more recent and expansive concept of "Corporate Social Responsibility." Numerous names have been given to it—Corporate Citizenship, Global Civic participation, Resilient Purchasing Accounting, Corporate Environmental Performance, Business Ethics, and Triple Bottom Line—but very few of us really understand it.